الإختلاف و مقارنة المذاهب عن نكاح المتعة عند العلماء الشيعة و أهل السنة - Hermanto, Agus (al-'adalah, 2016)
Abstract: Nikah Mut’ah (Temporary Marriage) in the Views of Sunni and Shi’i Clerics. This article analyses the different views between Sunni and Shi’i Clerics on the legitimacy of Nikah Mut’ah (Temporary Marriage). Even if both the Sunni and Shi’i clerics agree that the marriage practices were permitted by Prophet Muhammad (PBUH) during his lifetime, the two sides disagree whether or not the marriage is still allowed today. The Imami clerics argue that Nikah Mut’ah was legal only in the Prophet era. In their opinions the temporary marriages is allowed in Islam, for those in traveling or in  a certain conditions .and the permission is still valid until an unspecified time. The majority of Sunni scholars, however, reject the notions, referring to a hadith that Prophet Muhammad had banned the practices of Mut’ah soon after the Battle of Hunain. الملخص: "الإختلاف و مقارنة المذاهب عن نكاح المتعة عند العلماء الشيعة و أهل السنة" ولا خلاف بين الفقهاء من السنيين والإماميين في أن نكاح المتعة كان موجودا في زمن النبيّ رخص به ولكن الخلاف بينهم. تقول الشيعة الإمامية أن المتعة كانت مباحة في صدر الإسلام أيام النبيّ وأبي بكر وصدر من إمرة عمر, وإن هذا الإباحة غير محددة بعدد, وإن المتعة تجوز في كل وقت ولكن إنسان مسافرا كان أومقيما متي استوفت شروطها. أما جمهور الفقهاء من أهل السنة (الحنفي والمالكي والشافعي والحنبلي) فإنهم يقولون إن مشروعية زواج المتعة منسوخة.